2003
DOI: 10.2174/1568006033481410
|View full text |Cite
|
Sign up to set email alerts
|

The Heme Oxygenase System: Its Role in Liver Inflammation

Abstract: Heme Oxygenase is the rate-limiting enzyme in the degradation of heme into carbon monoxide (CO), iron and bilirubin. To date, three heme oxygenase isozymes have been identified: HO-1, HO-2 and HO-3. While HO-1 is structurally different from its counterparts, HO-2 and HO-3 are very similar (90% homology), with HO-3 being a poor heme catalyst. Of the three isozymes, HO-1 is believed to be the only inducible form. Constitutively expressed HO-2 has been identified in several organs including kidney and vascular sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 0 publications
2
68
0
4
Order By: Relevance
“…The mechanism by which HO-1 confers protection against oxidative stress has not yet been fully understood. It has been suggested that HO-1 possesses antioxidant activity deriving from the elimination of prooxidant heme and from the biological activities of its reaction products: biliverdin, bilirubin and iron [22][23][24] . Both biliverdin and bilirubin possess antioxidant properties [25] , whereas iron released during heme catabolism can stimulate ferritin synthesis [26] .…”
Section: Basic Researchmentioning
confidence: 99%
“…The mechanism by which HO-1 confers protection against oxidative stress has not yet been fully understood. It has been suggested that HO-1 possesses antioxidant activity deriving from the elimination of prooxidant heme and from the biological activities of its reaction products: biliverdin, bilirubin and iron [22][23][24] . Both biliverdin and bilirubin possess antioxidant properties [25] , whereas iron released during heme catabolism can stimulate ferritin synthesis [26] .…”
Section: Basic Researchmentioning
confidence: 99%
“…[13][14][15][16] Accumulating evidence reveals the protective role of HO-1 by virtue of the antiinflammatory, antiapoptotic and antiproliferative activities of the products released by the heme breakdown reaction. [17][18][19] The acute phase response (APR) is a defense reaction of the organism directed to restrict the area of damage and to eliminate, or at least isolate, the damaging agent. Every agent that leads to loss of tissue integrity induces a local reaction known as inflammation.…”
mentioning
confidence: 99%
“…HO-1 catabolizes free heme into CO, biliverdin, and iron (20,21). According to many animal studies, HO-1 has protective effects against oxidative stress (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%